An Analysis of International Student Recruitment for UK Business Schools: A Chinese and Indian Cultural Perspective - Cooley, Victoria Laura (2008)
This study aims to contribute to the knowledge of understanding international higher education services within the UK, which is underpinned by marketing theories and serves to provide managerial implications for education marketers. This is undertaken within the specific context of Chinese and Indian's decision making process of choosing to study a UK business degree. The purpose of this dissertation is to systematically examine and critically evaluate literature in international higher education services, the consumers decision making process and underlying characteristic of Chinese and Indian culture which influences their decisions. A proposed model was developed based on the existing literature derived from the decision making process of international students and Chinese and Indian cultural value systems. Furthermore, the researcher empirically tested these frameworks on Chinese and Indian students' choice of behaviour, which in turn supports revised models. These serve to provide managerial implications for both UK higher educational institutions in general and business school management and marketers.